Estudo da sinterabilidade de ligas de níquel obtidas por meio dos portadores de liga sic, si3n4 ou si metálico com grafita - Nicodemo, Juliana Pivotto (2012)
Nickel alloys are frequently used in applications that require resistance at high temperatures associated with resistance to corrosion. Alloys of Ni-Si-C can be obtained by means of powder metallurgy in which powder mixtures are made of metallic nickel powders with additions of various alloying carriers for such were used in this study SiC, Si3N4 or Si metal with graphite. Carbonyl Ni powder with mean particle size of 11 mM were mixed with 3 wt% of SiC powders with an average particle size of 15, 30 and 50 μm and further samples were obtained containing 4 to 5% by mass of SiC with average particle size of 15 μm. Samples were also obtained by varying the carrier alloy, these being Si3N4 powder with graphite, with average particle size of 1.5 and 5 μm, respectively. As a metallic Si graphite with average particle size of 12.5 and 5 μm, respectively. The reference material used was nickel carbonyl sintered without adding carriers. Microstructural characterization of the alloys was made by optical microscopy and scanning electron microscopy with semi-quantitative chemical analysis. We determined the densities of the samples and measurement of microhardness. We studied the dissociation of carriers alloy after sintering at 1200 ° C for 60 minutes. Was evaluated also in the same sintering conditions, the influence of the variation of average particle size of the SiC carrier to the proportion of 3% by mass. Finally, we studied the influence of variation of the temperatures of sintering at 950, 1080 and 1200 ° C without landing and also with heights of 30, 60, 120 and 240 minutes for sintering where the temperature was 950 °C. Dilatometry curves showed that the SiC sintered Ni favors more effectively than other carriers alloy analyzed. SiC with average particle size of 15 μm active sintering the alloy more effectively than other SiC used. However, with the chemical and morphological analyzes for all leagues, it was observed that there was dissociation of SiC and Si3N4, as well as diffusion of Si in Ni matrix and carbon cluster and dispersed in the matrix, which also occurred for the alloys with Si carriers and metallic graphite. So the league that was presented better results containing Si Ni with graphite metallic alloy as carriers, since this had dispersed graphite best in the league, reaching the microstructural model proposed, which is necessary for material characteristic of solid lubricant, so how we got the best results when the density and hardness of the alloy